Endometrial DNA methylation signatures during the time of breeding in relation to the pregnancy outcome in postpartum dairy cows fed a control diet or supplemented with rumen-protected methionine - Salilew-Wondim, Dessie; Tholen, Ernst; Held-Hoelker, Eva; Shellander, Karl; Blaschka, Carina; Drillich, Marc; Iwersen, Michael; Suess, David; Gebremedhn, Samuel; Tesfaye, Dawit; Parys, Claudia; Helmbrecht, Ariane; et al. (Frontiers in Genetics, 2024)
Post calving metabolic stress reduces the fertility of high producing dairy cows possibly by altering the expression of genes in the maternal environment via epigenetic modifications. Therefore, this study was conducted to identify endometrial DNA methylation marks that can be associated with pregnancy outcomes in postpartum cows at the time of breeding. For this, twelve days post-calving, cows were either offered a control diet or supplemented daily with rumen-protected methionine. Cows showing heat 50–64 days postpartum were artificially inseminated. Endometrial cytobrush samples were collected 4–8 h after artificial insemination and classified based on the pregnancy out comes as those derived from cows that resulted in pregnancy or resulted in no pregnancy. The DNAs isolated from endometrial samples were then subject to reduced representative bisulfite sequencing for DNA methylation analysis. Results showed that in the control diet group, 1,958 differentially methylated CpG sites (DMCGs) were identified between cows that resulted in pregnancy and those that resulted in no pregnancy of which 890 DMCGs were located on chr 27: 6217254–6225600 bp. A total of 537 DMCGs were overlapped with 313 annotated genes that were involved in various pathways including signal transduction, signalling by GPCR, aldosterone synthesis and secretion. Likewise, in methionine supplemented group, 3,430 CpG sites were differentially methylated between the two cow groups of which 18.7% were located on Chr27: 6217254–6225600 bp. A total of 1,781 DMCGS were overlapped with 890 genes which involved in developmental and signalling related pathways including WNT-signalling, focal adhesion and ECM receptor interaction. Interestingly, 149 genes involved in signal transduction, axon guidance and non-integrin membrane-ECM interactions were differentially methylated between the two cow groups irrespective of their feeding regime, while 453 genes involved in axon guidance, notch signalling and collagen formation were differentially methylated between cows that received rumen protected methionine and control diet irrespective of their fertility status. Overall, this study indicated that postpartum cows that could potentially become pregnant could be distinguishable based on their endometrial DNA methylation patterns at the time of breeding.